1996
DOI: 10.1016/0375-9474(96)00034-6
|View full text |Cite
|
Sign up to set email alerts
|

Parity violation in quasielastic electron scattering from closed-shell nuclei

Abstract: The electromagnetic and weak neutral current matrix elements that enter in the analysis of parity-violating quasielastic electron scattering are calculated using a continuum nuclear shell model. New approximations to the on-shell relativistic one-body currents and relativistic kinematics for use in such models are developed and discussed in detail. Results are presented for three closed-shell nuclei of interest: 16 O, 40 Ca and 208 Pb. The current work concludes with a study of the sensitivity of the resulting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
155
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(168 citation statements)
references
References 35 publications
13
155
0
Order By: Relevance
“…The SR approach includes important relativistic ingredients in the current operator. This has been already illustrated in previous works [9,15,64,65], and it is also clearly shown by results in Fig. 14 corresponding to the plane-wave limit; the fully relativistic and the SR calculations lead to very similar curves in spite of using different descriptions of the initial bound nucleon wave functions: solutions of the Dirac-Hartree model and the Schrödinger equation with a Woods-Saxon potential, respectively.…”
Section: B Inclusive Qe Charged-current (ν µ) Reactionssupporting
confidence: 77%
“…The SR approach includes important relativistic ingredients in the current operator. This has been already illustrated in previous works [9,15,64,65], and it is also clearly shown by results in Fig. 14 corresponding to the plane-wave limit; the fully relativistic and the SR calculations lead to very similar curves in spite of using different descriptions of the initial bound nucleon wave functions: solutions of the Dirac-Hartree model and the Schrödinger equation with a Woods-Saxon potential, respectively.…”
Section: B Inclusive Qe Charged-current (ν µ) Reactionssupporting
confidence: 77%
“…Although extensive tests showing the reliability of the SR expansion [12] have been performed within the context of the RFG and RPWIA approaches, the effects introduced by the dynamical enhancement of the lower components in the Dirac spinors [13][14][15], accounted for within a fully relativistic calculation, are not present in the SR approaches and this may be the reason that the fully relativistic and the SR calculations for the scaling function differ. From previous studies [6,7], we have shown that the scaling function is very slightly modified by the dynamical relativistic effects linked to the initial bound nucleon states.…”
mentioning
confidence: 99%
“…with E and p = √ E 2 − M 2 the nucleon energy and momentum, E max = E Λ − m π , the maximum nucleon energy, neglecting the recoil of the nucleus, and R lj (p; r) a continuum solution of the nucleon Schrödinger equation [32], with the same potential as that used for the bound nucleons to compute the discrete contribution to the decay width. The nucleon wave function normalization in the continuum is the same as that given above for the pions (Eqs.…”
mentioning
confidence: 99%